2010
DOI: 10.5688/aj740222
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fidelity Simulation Mannequin to Introduce Pharmacy Students to Advanced Cardiovascular Life Support

Abstract: Objective. To design and implement an advanced cardiac life support (ACLS) workshop featuring a human patient simulator (HPS) for third-year pharmacy students. Design. The ACLS workshop consisted of a pre-session lecture, a calculation exercise, and a 40-minute ACLS session using an HPS. Twenty-four 5-member teams of students were assigned roles on a code team and participated in a ventricular fibrillation/pulseless ventricular tachycardia case. Assessment. Students completed an anonymous postactivity survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 22 publications
5
84
1
Order By: Relevance
“…Five articles were identified in which human-patient simulation (HPS) technology with mannequin models 17 The assessment of the HPS tool included presimulation and postsimulation quizzes, examination scores, grading of the simulation activity, and blood pressure and pulse assessments. Student satisfaction data was collected using postcourse/simulation surveys.…”
Section: Human-patient Simulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Five articles were identified in which human-patient simulation (HPS) technology with mannequin models 17 The assessment of the HPS tool included presimulation and postsimulation quizzes, examination scores, grading of the simulation activity, and blood pressure and pulse assessments. Student satisfaction data was collected using postcourse/simulation surveys.…”
Section: Human-patient Simulationmentioning
confidence: 99%
“…13 Grades specific to the simulation were high and significantly improved (p50.029), 14 including blood pressure measurement accuracy (p,0.05); 14 but in another study using HPS, median scores on knowledge-based questions in advanced cardiac life support were low. 17 Students were able to correctly calculate medication rates (78%), but struggled with concentration calculations (20%) and questions relating to asystole or pulseless electrical activity (21.8%) and ventricular tachycardia (11.7%). 17 Results from an HPS study on myocardial infarction were higher, with an average examination score of 88% reported.…”
Section: Human-patient Simulationmentioning
confidence: 99%
See 3 more Smart Citations